Sol-Gel Derived Titania Coating on Titanium Substrate: Sol-gel derived titania coating - Latifi, Afrooz; Afshar, Abdollah; Behnamghader, Aliasghar; Joughehdoust, Sedigheh (Iranian Journal of Pharmaceutical Sciences, 2008)
The synthesis of titania via sol-gel method has been widely studied. In thepresent work, titania was deposited onto a titanium substrate via sol-gel method.Different processing parameters such as the repetition number of dipping/heattreatment process and dipping time have been studied to obtain the homogenous titaniacoating. Phase and microstructural evaluation of the powder and coating sampleswere performed, using X-ray diffraction and scanning electron microscopy. Theparticle size distribution of the powder was measured by zetasizer instrument.Based on the results obtained in this work, both rutile and anatase phases formedafter the heat treatment at 600 °C. In addition, the thickness and the morphologyof the coatings were found to be influenced by the repetition number of process.